Comparison of Pulmonary Artery Pressure Measurement With Doppler Echocardiography or With Right Heart Catheterization in Patients With Congenital Heart Disease - Yin, Dan; Wang, Ying; Zheng, Min; Wei, Huijing; Li, Mi; Lv, Tiewei; Bai, Yonghong; Tian, Jie; Wu, Xiaoyun (Frontiers in Pediatrics, 2019)
Background: Doppler echocardiography (D-ECHO) is a commonly used imaging tool for both diagnosis and follow-up examination of congenital heart disease (CHD). The goal of this study is to evaluate the accuracy of D-ECHO as used to measure an estimate sPAP in pediatric patients with CHD. Methods: A prospective study in 397 pediatric patients with CHD has been carried out to compare estimate sPAP measured with D-ECHO to that measured with right heart catheterization (RHC). Pearson correlation analyses were used to calculate the correlation coefficients between RHC and D-ECHO. Bland-Altman analyses were carried out to assess the agreement between the two methods. Results: Our data have demonstrated a significant underestimation of sPAP by DECHO compared to that by RHC. A strong correlation (r = 0.957, p < 0.01) was found between sPAP (36.1±14.9 mmHg) and RVSP (36.0±14.5 mmHg) measured with RHC. However, a relatively weak correlation (r = 0.219, p < 0.01) was observed between sPAP (36.1 ± 14.9 mmHg) measured during RHC and sPAP (28.7±9.7 mmHg) as estimated using D-ECHO. The Bland-Altman analysis demonstrated that the bias for D-ECHO sPAP estimates was 6.6 mmHg with 95% limits of agreement ranging from - 23.6 mmHg to 36.8 mmHg. A total of 57.5% of D-ECHO measurements were found to be accurate, with accuracy predefined as 95% of agreement within ±10 mmHg for sPAP estimates